A Lithography‐Free and Field‐Programmable Photonic Metacanvas. Issue 5 (11th December 2017) - Dong, Kaichen; Hong, Sukjoon; Deng, Yang; Ma, He; Li, Jiachen; Wang, Xi; Yeo, Junyeob; Wang, Letian; Lou, Shuai; Tom, Kyle B.; Liu, Kai; You, Zheng; et al.
Abstract: The unique correspondence between mathematical operators and photonic elements in wave optics enables quantitative analysis of light manipulation with individual optical devices. Phase‐transition materials are able to provide real‐time reconfigurability of these devices, which would create new optical functionalities via (re)compilation of photonic operators, as those achieved in other fields such as field‐programmable gate arrays (FPGA). Here, by exploiting the hysteretic phase transition of vanadium dioxide, an all‐solid, rewritable metacanvas on which nearly arbitrary photonic devices can be rapidly and repeatedly written and erased is presented. The writing is performed with a low‐power laser and the entire process stays below 90 °C. Using the metacanvas, dynamic manipulation of optical waves is demonstrated for light propagation, polarization, and reconstruction. The metacanvas supports physical (re)compilation of photonic operators akin to that of FPGA, opening up possibilities where photonic elements can be field programmed to deliver complex, system‐level functionalities. Abstract : An all‐solid, rewritable metacanvas is demonstrated by exploiting the hysteretic phase transition of vanadium dioxide. On the metacanvas, nearly arbitrary metaphotonic devices can be rapidly and repeatedly written and erased. The writing is performed with a low‐power laser below 90 °C. Dynamic manipulation of optical waves for light‐beam steering, polarization control, and holographic reconstruction is achieved with the metacanvas.